2020
DOI: 10.1177/1535370220972024
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two molecular subtypes of dysregulated immune lncRNAs in ovarian cancer

Abstract: Long non-coding RNA (lncRNA) has increasingly been identified as a key regulator in pathologies such as cancer. Multiple platforms were used for comprehensive analysis of ovarian cancer to identify molecular subgroups. However, lncRNA and its role in mapping the ovarian cancer subpopulation are still largely unknown. RNA-sequencing and clinical characteristics of ovarian cancer were acquired from The Cancer Genome Atlas database (TCGA). A total of 52 lncRNAs were identified as aberrant immune lncRNAs specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Remarkably, stromal cell activity is also deregulated by ECM abnormalities which promotes inflammation as well as angiogenesis resulting in the formation of cancer microenvironments. The ECM-receptor interaction signal pathway has also been identified as a contributor to cancer progression with low survival rate in many gynecological malignancies including endometrial cancer, breast cancer and ovarian cancer ( Bao et al, 2019 ; Liu et al, 2021 ; Yadav et al, 2020 ). In this study, the expression of COL3A1 , COL5A1 and COL5A2 were downregulated in EC, are of the collagen family, and they interact with elements of the extracellular matrix (ECM) including matrix metalloproteinases, tyrosine kinase receptors, integrins, and signaling pathways to affect the behavior and activity of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, stromal cell activity is also deregulated by ECM abnormalities which promotes inflammation as well as angiogenesis resulting in the formation of cancer microenvironments. The ECM-receptor interaction signal pathway has also been identified as a contributor to cancer progression with low survival rate in many gynecological malignancies including endometrial cancer, breast cancer and ovarian cancer ( Bao et al, 2019 ; Liu et al, 2021 ; Yadav et al, 2020 ). In this study, the expression of COL3A1 , COL5A1 and COL5A2 were downregulated in EC, are of the collagen family, and they interact with elements of the extracellular matrix (ECM) including matrix metalloproteinases, tyrosine kinase receptors, integrins, and signaling pathways to affect the behavior and activity of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing the unique categories and subclasses of TIME in patients' tumors, the ability to predict and guide immunotherapeutic responses could be improved, and new therapeutic targets will be revealed [39] . The OC classification based on immune-related lncRNAs [40] and the glioma prognostic model based on m6A/m5C/m1A/m7G related lncRNAs have been reported [41] . M6A/m5C/m1A/m7G-related lncRNA has not yet been applied to explore the classification of OC.…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al [32] used weighted gene co-expression network analysis (WGCNA) and found that the expression levels of 4 lncRNAs could be used as independent immune prognostic factors for OC. Liu et al [33] identified 52 lncRNAs as ovarian cancer-specific immune lncRNA and redefined two different molecular subtypes. Different from the existing researches, we established a Fig.…”
Section: Discussionmentioning
confidence: 99%